The Role of E-commerce in Transforming Retail Business Models: Challenges and Opportunities - Thabo Nkosi; Amina Diallo; Malik Ndlovu; Fatoumata Keita (International Journal of Economics, Commerce, and Management, 2024)
This paper examines the transformative impact of e-commerce on traditional retail business models. By analyzing case studies of retailers that have successfully adapted to the digital marketplace, the study identifies key challenges, such as logistics and customer engagement, as well as opportunities for growth and innovation. The findings underscore the necessity for retailers to embrace digital strategies to remain competitive in the evolving market landscape.